The Concept Of Education In The West And Islam - Millah Kamelia*; Muhammad Bagas Fadli; Nurul Fadila Irdayu (Institut Agama Islam Negeri Kerinci, 2022)
Education is one of the most important elements for the formation of character and the builder of a nation's civilization. There are three factors in the formation of a civilization, namely the view of life, science and one of them is education. This paper aims to describe the conceptual differences between Western Education and Islamic Education. In accordance with the research methodology used in this study, namely: library researchis to collect, books, papers, articles and other references. Based on the results of the analysis that has been carried out, it can be concluded that the differences in the paradigms of Western and Islamic education are: In the ontological realm, the differences in education are seen mainly in the scope and nature of education itself. For the West, the scope and nature of education is limited to the visible aspects (empirical-positivistic), While Islamic education covers a more holistic scope, in addition to the empirical area (al-syahadah) but also in the area of meaning (al-ghaib). Then in the epistemological realm, the difference between the two lies in the source of knowledge, in Islam the source of education is the Qur'an, hadith and ijma'. While in the west the source is life experience. Axiologically, Western education does not make valuesÂ Â as part of educational outcomes, but as an effort to mature children, while Islam positions values as substantive in education.